From the theory of incommesurability to the myth of writting: Rancière and the politics of dissent - de Murcia Conesa, Antonio (Res Publica. Revista de Historia de las Ideas Políticas, 2015)
This paper discusses the relationship between the concepts of politics and aesthetic regime in the Rancière’s philosophy. First we interpret the opposition between politics and policy according to the concepts of incommensurability and mésentente. Just as the geometric rapport between incommensurable ratios underlies the policy and state administration, the rhetoric of misunderstanding becomes the model of a democratic politics largely sustained on an aesthetic consensus. Expelled from politics and confined to a representative ethical regime of art, classical rhetoric was replaced in modernity by aesthetical education. An essential part of the work of Rancière explains how the modern aesthetic regime helped to redefine the political subjectivity and to propose new forms of consensus. To understand his argument we discusses Rancière’s analysis of the concept of poeticity, directly confronted with the classical poetry, as well as its democratic reinterpretation of the myth of writing, which links to a democratic conception of the spirit and culture.
Keywords: Political philosophy; Democracy; Poetics; Aesthetics; Incommesurability; Rhetoric.